2014
DOI: 10.1021/ml500266x
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Tethers Mimicking Subunits of Polysaccharide Ligands: Selectin Antagonists

Abstract: We report on the design and synthesis of molecules having E- and P-selectins blocking activity both in vitro and in vivo. The GlcNAc component of the selectin ligand sialyl Lewis(X) was replaced by an acyclic tether that links two saccharide units. The minimization of intramolecular dipole-dipole interactions and the gauche effect would be at the origin of the conformational bias imposed by this acyclic tether. The stereoselective synthesis of these molecules, their biochemical and biological evaluations using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The experimentally confirmed inhibitors published in the articles by Calosso et al. (2014) ) and Gouge-Ibert et al.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The experimentally confirmed inhibitors published in the articles by Calosso et al. (2014) ) and Gouge-Ibert et al.…”
Section: Resultssupporting
confidence: 52%
“…Nonetheless, while IC 50 values allow for a straightforward comparison of the inhibitors within a single study, they cannot be used to compare inhibitors among the different studies due to the various experimental conditions. To deal with this issue, the logarithm of the ratio of IC 50 of a compound to IC 50 of sLe x was used ( Calosso et al. 2014 ) \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} \log \left(\mathrm{ratio}\right)=\log \left(\frac{IC_{50,{\mathrm{sLe}}^{\mathrm{X}}}}{IC_{50,\mathrm{cpd}}}\right).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was shown that sialic acid had little effect on the binding to E-selectin [48,343]. Thus, it was suggested to replace the GlcNAc residue with an acyclic tether with defined conformational bias [344], which led to the design and synthesis of selectin antagonists that exhibited the required activity both in vitro and in vivo [345]. Recently, several E-selectin inhibitors that have potential for anti-inflammatory drug development were designed with an approach that targets neighboring regions of the binding site [346].…”
Section: Glycomimetic Inhibitorsmentioning
confidence: 99%
“…Ethyl 2,3,4,6-tetra-O-acetyl-1-thio-α-d-mannopyranoside (4) Ethyl 2,3,4,6-tetra-O-acetyl-1-thio-α-d-mannopyranoside (4) was synthesized following a slightly modified protocol reported by Calosso M. et al [43].…”
Section: Chemical Synthesis Of Monosaccharides 2-9mentioning
confidence: 99%